Pendidikan Karakter dalam Membentuk Kepribadian Santri (Studi Analisis di Pondok Pesantren Darul Ulum Sumber Baru Sokobanah Sampang) - Akhmad Faisal (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2022)
The emergence of various problems in the midst of society is definitely related to the moral quality in it. Social problems currently occur in almost all orders of society, even in the world of education. Bullying, theft, molestation and various other violence have been attached to the world of education. It is a dark face of the Indonesian education world that shows that the noble personality values in students have begun to fade. Therefore, this paper will in depth examine the process of character education in shaping the personality of students at PP. Darul Ulum Sumber Baru Sokobanah Sampang Madura. Character education must be supported by qualified environmental conditions, especially for a teacher who is required to have a noble personality that it can have a positive influence on the character and identity of the students. This paper will answer at least two main points—how character education planning at Darul Ulum Islamic Boarding School Sumber Baru Sokobanah Sampang is and what the effect on the personality of the santri is. The description in this paper will use a qualitative approach and descriptive writing for further data explaination obtained through interviews, observation and documentation. From an in-depth study of the problems, it was found that Pesantren Darul Ulum succeeded in internalizing character values outside of formal school hours in the form of extracurricular programs through several pesantren activities, both learning, recitation and other santri’s religious activities. In the end, students are able to apply the ten character values absorbed from the surrounding environment, so that it get better, more religious, for their personalities, then in the end it will lead them to get better achievements.